The Use of National Heritage in Visual Arts Education: Pedagogical Opportunities - Raxmonova Mahliyo Zoir qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article analyzes the pedagogical significance of using national heritage in visual arts education. It explores how incorporating national motifs, colors, and traditional patterns in lessons helps develop students’ aesthetic taste, creative thinking, and understanding of cultural values. The paper also presents effective methods for integrating national heritage into contemporary teaching practices using modern pedagogical technologies.